2002
DOI: 10.1002/1521-396x(200211)194:1<112::aid-pssa112>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ar Gas Dilution in Methane Plasma on the Properties of Diamond-like Carbon Films

Abstract: Diamond‐like carbon films have been deposited with different amounts of Ar gas dilution of a methane precursor by the radio frequency plasma enhanced chemical vapor deposition technique. The object of this work is to study the effects of Ar dilution on the film properties. Optical, IR and Raman spectroscopy, along with hardness tests, have been performed for this purpose. The optical bandgap, hardness and the integrated intensity ratio (ID/IG) of the Raman D‐line and the G‐line, respectively, tend to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The CH 4 gas was effectively dissociated by electron and Ar metastable atom impact in penning discharge model, creating sufficient CH 𝑥 radicals. [14,15] It is consistent with the results in Ref. [16], in which the mass spectrometry (MS) measurements show a high concentrations of multi-carbon ions (such as C 2 ) in plasma phase when inert gas is added.…”
Section: Speciessupporting
confidence: 88%
“…The CH 4 gas was effectively dissociated by electron and Ar metastable atom impact in penning discharge model, creating sufficient CH 𝑥 radicals. [14,15] It is consistent with the results in Ref. [16], in which the mass spectrometry (MS) measurements show a high concentrations of multi-carbon ions (such as C 2 ) in plasma phase when inert gas is added.…”
Section: Speciessupporting
confidence: 88%
“…They found that the sp 3 al. [13] investigated the influence of Ar gas dilution in methane plasma on the properties of diamond-like carbon films and pointed out that the sp 3 fraction in the films increased with increasing Ar fraction in the precursor. Kimura et al [14] found that the films synthesized under hydrogen plasma had the largest sp 3 /sp 2 ratio by studying microstructure of diamond-like carbon films prepared by cathodic arc deposition under different circumstances.…”
Section: Introductionsupporting
confidence: 86%
“…In the same time, the mechanical properties of their DLC films deteriorated, which indicates a graphitization of the films. Chakrabarti et al44 noticed a similar behavior by increasing the Ar content in a capacitively coupled methane RF plasma up to 9:1, for a pressure of 40 Pa, constant power (150 W), and constant total flow (100 sccm). Both qualified the sharp drop in the deposition rate at higher inert gas‐to‐monomer ratios to ion‐induced sputtering effects.…”
Section: Resultsmentioning
confidence: 79%